Epistemic Construct of nature as a subject of rights in public international law - Mendoza Escalante, Pablo Ricardo (2025)
This research develops an analysis of the epistemic construction of nature as an approach to being a subject of rights in international public law. To this end, three objectives are proposed to answer the question: What is required to propose an epistemic construct of nature as a subject of rights in the international sphere that modifies the classic legal framework? To this end, a type of documentary research with a descriptive qualitative approach was used. The first objective was to delve into existing theories on subjects of rights; the second objective describes the elements that structure nature as a subject, and the third objective designs the proposed epistemic construct. To this end, the position of subject and legal subject is studied from the rational and positivist Western model, where the power of will and the interest of the individual subject of rights converge. This position is compared with approaches that advocate for the defense of the rights to nature, considered biocentric and/or ecocentric approaches, contrary to the anthropocentric paradigm. The article concludes by proposing that nature is a subject of rights in public international law as an epistemic construct; it is concluded that there are theoretical, epistemic, and legal elements that determine nature as a subject of rights in public international law.